IMPROVE ACCOUNT -BOOKS AUDIT PLANNING WITH STAFF (Marketing Journal, 2025)
This article highlights issues related to improving the planning of audits of employee settlements. In particular, it proposes a working paper for evaluating the internal control system related to employee settlements, a procedure for assessing internal co ntrol by elements, criteria for evaluating the reliability of internal control, a sample list of procedures for collecting audit evidence, as well as an audit plan and audit program.
Keywords: audit inspection; tasks resolved during the audit; audit evidence; audit procedures; internal control; evaluation criteria; audit program